TECHNICAL SPECIFICATIONS FOR UAVs FOR 3D TERRAIN MAPPING - Oksana Udovytska (Modern American Journals, 2025)
This article summarizes the current technical requirements and architectural solutions for unmanned aerial vehicles (UAVs, drones) intended for three-dimensional terrain mapping (photogrammetry, LiDAR, visual-optical SLAM systems). Recommendations are provided regarding platform selection, sensors (cameras, LiDAR, IMU, GNSS/RTK/PPK), survey parameters (GSD, overlaps, trajectories), data processing (SfM–MVS, LiDAR pipelines, visual-inertial filters), and accuracy assessment.
Keywords: Unmanned aerial vehicles (UAVs), drones, 3D mapping, photogrammetry, LiDAR, visual-inertial systems (VIO, SLAM), inertial measurement unit (IMU), georeferencing accuracy, digital terrain model (DTM).